2014
DOI: 10.4236/abb.2014.54036
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Laboratory Mice for the High Scores of Logic Task Solutions: The Correlated Changes in Behavior

Abstract: Genetically heterogenous mouse population served as the basis for experiment designed to select mice for the high levels of extrapolation ability. Extrapolation task (which belongs to the category of cognitive tasks) was the following: hungry and thirsty mouse was placed in the experimental box facing the cup with milk which could be reached via the small opening in the frontal wall. After several seconds of drinking the food moved behind this wall to the right or to the left and disappeared from animal view. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Mice tested in this experiment belonged to F28, when the selection was discontinued for seven generations. Previously, it was demonstrated that SB mice (in all three replications of brain weight selection experiments) were consistently more fearful than LB animals (see Perepelkina et al, 2014). Thus, they presumably would be more eager to escape into the safe dark compartment, while the less fearful LB mice were more successful in the puzzle-box test performance.…”
Section: "Puzzle Box" Test Experiments With Lb and Sb Micementioning
confidence: 81%
See 1 more Smart Citation
“…Mice tested in this experiment belonged to F28, when the selection was discontinued for seven generations. Previously, it was demonstrated that SB mice (in all three replications of brain weight selection experiments) were consistently more fearful than LB animals (see Perepelkina et al, 2014). Thus, they presumably would be more eager to escape into the safe dark compartment, while the less fearful LB mice were more successful in the puzzle-box test performance.…”
Section: "Puzzle Box" Test Experiments With Lb and Sb Micementioning
confidence: 81%
“…The puzzle box test (for details see Ben-Abdallah et al, 2011;Perepelkina et al, 2014), is a modified version of the "Light-Dark" test, in which an animal is placed into the brightly lit part of a box and must find the way to escape into the darkness; the route to the dark compartment (goal box) was via an underpass (4 x 2 x 15 cm) 2 (see Fig. 9).…”
Section: "Puzzle Box" Test Experiments With Lb and Sb Micementioning
confidence: 99%